Designed Reactive Natural Deep Eutectic Solvents for Lipase-Catalyzed Esterification - Alina Ramona Buzatu; Anamaria Todea; Raluca Pop; Diana Maria Dreavă; Cristina Paul; Ioan Bîtcan; Marilena Motoc; Francisc Peter; Carmen Gabriela Boeriu (Molecules)
Natural deep eutectic solvents (NADESs) are a sustainable, green option for extraction and reaction media in biorefineries and various chemical and biotechnological applications. Particularly, enzymatic reactions profit from NADES applications, as these solvents help to maintain high substrate solubility while improving both enzyme stability and efficiency. Recent studies confirmed that NADESs can perform multiple functions simultaneously, as reaction media for biocatalytic conversions, but also as substrates and catalysts for reactions, fulfilling the role of a reactive solvent. This study reports the beneficial effect of designed reactive natural deep eutectic solvents (R-NADESs) on the esterification activity and thermal stability of free and immobilized lipases in the synthesis of polyol- and carbohydrate-based biosurfactants. We manufactured and characterized 16 binary and ternary R-NADES systems with choline chloride (ChCl) as the hydrogen bond acceptor (HBA) and carbohydrate polyols; mono-, di-, and oligosaccharides; urea (U); N-methyl urea (MU); and water as the hydrogen bond donors (HBDs), in different combinations and molar ratios, most of which are reported for the first time in this paper. We determined their physicochemical, thermal, and molecular properties, including among others viscosity, polarizability, and the number of hydrogen bonds, and we showed that these properties are controlled by composition, molar ratio, molecular properties, temperature, and water content. Many lipases, both native and immobilized, showed high stability and remarkable catalytic performance in R-NADESs during esterification reactions.